2015
DOI: 10.3389/fpsyg.2015.01213
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stimulus repetition on duration judgments with simple stimuli

Abstract: Two experiments investigated the effects of stimulus repetition vs. stimulus novelty on perceived duration. In a reminder task, a standard and a comparison stimulus were presented consecutively in each trial, and the comparison was either a repetition of the standard or a different stimulus. Pseudowords (Experiment 1) or strings of consonants (Experiment 2) were used as stimuli and the inter-stimulus interval (ISI) between the standard and the comparison was either constant or variable. Participants were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
6
21
1
Order By: Relevance
“…A one-way repeated-measures ANOVA showed that the mean PSE was significantly higher for the repeated than the novel condition, F (1, 11) = 6.94, p < 0.05, η p 2 = 0.39, showing a shortened perceived duration for the repeated character than the novel character. The finding is consistent with the literature (Birngruber et al, 2015b;Matthews, 2011;Matthews & Gheorghiu, 2016). The discrimination sensitivities, measured by the JNDs, failed to find any difference between two conditions, F (1, 11) = 1.41, p = 0.26, η p 2 = 0.11, BF = 0.59.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…A one-way repeated-measures ANOVA showed that the mean PSE was significantly higher for the repeated than the novel condition, F (1, 11) = 6.94, p < 0.05, η p 2 = 0.39, showing a shortened perceived duration for the repeated character than the novel character. The finding is consistent with the literature (Birngruber et al, 2015b;Matthews, 2011;Matthews & Gheorghiu, 2016). The discrimination sensitivities, measured by the JNDs, failed to find any difference between two conditions, F (1, 11) = 1.41, p = 0.26, η p 2 = 0.11, BF = 0.59.…”
Section: Resultssupporting
confidence: 92%
“…Our subjective time is susceptible to many factors, such as nontemporal properties, attention, emotion, action and intention, and prior experience (Allman, Teki, Griffiths, & Meck, 2014;Droit-Volet & Gil, 2009;Ganzenmüller, Shi, & Müller, 2012;Jia, Shi, & Feng, 2015;Matthews & Meck, 2016;Shi & Burr, 2016;Shi, Church, & Meck, 2013;Shi, Ganzenmüller, & Müller, 2013;Xuan, Zhang, He, & Chen, 2007). The latter, prior experience, causes various types of time distortions, such as spatialspecific duration compression (Johnston, Arnold, & Nishida, 2006), central tendency of duration judgment (Gu, Jurkowski, Shi, & Meck, 2016;Jazayeri & Shadlen, 2010;, odd-ball time dilation (Pariyadath & Eagleman, 2007;Tse, Intriligator, Rivest, & Cavanagh, 2004), and repetition compression (Birngruber, Schröter, & Ulrich, 2015b;Matthews, 2011;Matthews & Gheorghiu, 2016). One remarkable example is that repeating of the first item only once suffices to shortens the apparent duration (Birngruber et al, 2015b;Matthews, 2011), while the first item in a train of repeated displays seems longer than the subsequent items (Rose & Summers, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was difficult to adopt a curve-fitting procedure (e.g., utilizing Gaussian function) for the estimation of PSE SL-LS because the results obtained from 10 (four from French-speaking and six from Japanese-speaking) participants did not conform to a bell-shaped function (i.e., showed no clear peak). 4 Alternatively, we estimated PSE SL-LS with the following formula according to the arithmetic average method (Guilford, 1954), which was equivalent with the estimation of the first moment in the waveform moment analysis (Birngruber, Schröter, & Ulrich, 2015;Cacioppo & Dorfman, 1987):…”
Section: Discussionmentioning
confidence: 99%